2017
DOI: 10.21577/0103-5053.20170208
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4- and 1,3,4-Oxadiazoles as Scaffolds in the Development of Antiparasitic Agents

Abstract: In this review, we present the potential use of the heterocyclic oxadiazole rings in the design and synthesis of new drugs to treat parasitic infections. We intend to compare herein all the four isomeric forms of oxadiazole rings as well as discuss the differences and similarities between them. In addition, we discuss aspects on their reactivity that justify the great importance of both 1,2,4-and 1,3,4-oxadiazoles isomers when compared with their other two isomers. Although some oxadiazole isomers satisfy Hück… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…Although the number of examples was too low to establish a reliable ranking between the various links, the present results suggested that 1,2,4‐oxadiazole and 1,2,4‐triazole rings could be as favorable as the peptide bond. As stated above, the observed variation in inhibitory potencies between compounds only differing by the heterocyclic link probably originated from the different aromatic, electrostatic, and hydrogen bonding properties of the three heterocycles …”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Although the number of examples was too low to establish a reliable ranking between the various links, the present results suggested that 1,2,4‐oxadiazole and 1,2,4‐triazole rings could be as favorable as the peptide bond. As stated above, the observed variation in inhibitory potencies between compounds only differing by the heterocyclic link probably originated from the different aromatic, electrostatic, and hydrogen bonding properties of the three heterocycles …”
Section: Resultsmentioning
confidence: 83%
“…Although the three heterocyclic moieties are similar in size and shape and present the two substituents in very similar positions, they show variations in aromatic, electrostatic, and hydrogen bonding properties. This could lead to different binding modes with the target, and therefore to variation in inhibitory potencies between compounds only differing by the heterocyclic moiety …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxadiazole nucleus presents four isomers ( Figure 1); however, one of them, the 1,2,3-oxadiazole isomer, is not of any practical use, as it is unstable and decomposes easily. 4 Although the 1,2,4-oxadiazole heterocycle was first synthesized in 1884, 5 it was only in the 1990s that this nucleus aroused interest within the scientific community. 6 The literature reports a diverse set of applications for the 1,2,4-oxadiazole core in medicinal chemistry, 7,8 such as antiasthmatic, 9 antidiabetic, 10 antitumoral, 11 anti-inflammatory, 12 antioxidant, 12 and antimicrobial.…”
Section: Introductionmentioning
confidence: 99%